2006
DOI: 10.1007/s10654-006-9000-6
|View full text |Cite
|
Sign up to set email alerts
|

Habitual green tea consumption and risk of an aneurysmal rupture subarachnoid hemorrhage: A case–control study in Nagoya, Japan

Abstract: In a case-control study in Japan, we found that habitual green tea consumption may be strongly associated with a reduced risk for SAH. Our findings will be useful in targeting individuals and populations for the primary prevention of SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Similarly, we did not find any association between a high consumption of caffeinated coffee or tea and the risk of SAH, which contradicts studies from Japan and Finland [20,22,24], although caffeine has modest hypertensive effects which diminish over time as tolerance develops [34,46]. Of course, comparisons between studies are complicated by differences in the methods of dietary assessment, in particularly of food quantities, and the source of comparison controls.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Similarly, we did not find any association between a high consumption of caffeinated coffee or tea and the risk of SAH, which contradicts studies from Japan and Finland [20,22,24], although caffeine has modest hypertensive effects which diminish over time as tolerance develops [34,46]. Of course, comparisons between studies are complicated by differences in the methods of dietary assessment, in particularly of food quantities, and the source of comparison controls.…”
Section: Discussioncontrasting
confidence: 89%
“…There is limited data upon which to make dietary recommendations specifically for the prevention of subarachnoid hemorrhage (SAH) in high-risk individuals [20,21,22,23,24,25,26,27]. There may be specific dietary exposure that alone or in association with the two established risk factors for the condition, namely hypertension and smoking, may contribute to the formation and rupture of intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…One study 27 included only subjects with an intracerebral hemorrhage and another only included subarachnoid hemorrhage. 28 Because these are minority subsets of total stroke incidence, neither study was included in the meta-analysis, leaving only one case-control study in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have suggested that dietary antioxidants may play a protective role against the development of subarachnoid hemorrhage (SAH) (Marzatico et al, 1998;Leppala et al, 1999Leppala et al, , 2000Hirvonen et al, 2000;Kaynar et al, 2005;Okamoto, 2006;Okamoto and Horisawa, 2006). In general, various dietary antioxidants may be interactive or synergistic rather than isolated.…”
Section: Introductionmentioning
confidence: 99%